Nasogastric tube insertion in anesthetized, intubated adult patients: A comparison between combined lateral position with throat pack in situ and lateral position alone - Rajdeep Biswas; Soma Chakraborty; Sangita Mandal; Subha Sankar Das; Sarfraaz Rahman; Mandal, Mohanchandra (Asian Journal of Medical Sciences, 2024)
Background: Although the proper placement of nasogastric tube (NGT) is usually a simple procedure, it may be challenging one in case of its placement in anesthetized intubated patients. At times, it may be tiresome even for the expert anesthesiologist. Different techniques have varying success rates. Many novel techniques are entering the avenue to be tested. Combinations of different techniques are showing improved success rates over individual techniques. Aims and Objectives: This interventional study primarily aimed at comparing the success rates of proper placement of NGT in the first attempt between the “combined lateral position with throat pack in situ” and “lateral position alone.” Materials and Methods: The present study was performed on 180 adults (≥18 years), posted for abdominal surgeries requiring NGT insertion. Patients received NGT placement using the “combined lateral position with throat pack in situ” technique (Group A, n=80) or lateral position alone (Group B, n=80). The proportion of patients in whom correct placement of NGT was possible in the first attempt using either of the techniques (primary outcome), the procedure time for successful placement of NGT, and the incidence of adverse events were compared between the groups. Results: Correct placement of NGT in the first attempt was possible in considerably higher proportions of patients using the combined technique over lateral position alone (87.5% vs. 68.75%, P=0.007). The procedure time was comparable in both groups (23.7±6.6 vs. 25.2±5.2, combined vs. lateral position alone, P=0.093). Coiling was found to be considerably reduced in the combined method compared with the “lateral position alone” (8.75% vs.17.5%, P=0.03). Conclusion: Combined lateral position with throat pack in situ technique can be a better alternative to “lateral position alone” for NGT insertion in anesthetized, intubated adult patients.